Gastrointestinal complications in acute and chronic pancreatitis - Bansal, Akash (JGH Open, 2019)
Pancreatitis is one of the important medical conditions. Gastrointestinal (GI) complications of pancreatitis are important and lead to significant morbidity and mortality. Diagnosis of these complications is difficult and may require a strong clinical suspicion coupled with various imaging features. This review provides an extensive update of the whole spectrum of GI complication of pancreatitis, both acute and chronic, from inflammation, ischemia, and necrosis to obstruction, perforation, and GI fistulae. The focus is on the clinical and imaging features of this less commonly described aspect of pancreatitis.